The effect of influenza vaccine immunization on natural antibodies - Živković, Irena; Muhandes, Lina; Petrušić, Vladimir; Minić, Rajna; Dimitrijević, Ljiljana (Archives of Pharmacy, 2021)
Natural, polyreactive, low-affinity antibodies are known to play an important role not only in the immediate defense against pathogens, but also in shaping the acquired immune response. On the other hand, antigen specific, high-affinity antibodies can affect the balance of natural antibodies and lead to autoimmune diseases. In this study we have analyzed the changes that occur in the IgM and IgG pool of natural antibodies after immunization with split or whole virion influenza vaccine. For this purpose, “in-house” developed ELISAs were used. The subjects were divided, according to the vaccination status, into those who had been immunized with the influenza vaccine in previous years and those who had been immunized for the first time. The analysis indicated that the pool of natural antibodies was not impaired by the immunization, evidenced by the lack of changes in any of the groups, and that certain fluctuations were induced in order to maintain the homeostasis of the immune system.
Keywords: Natural antibodies; immunization; immune homeostasis